Effect of green GO/Au nanocomposite on in‐vitro amplification of human DNA. Issue 9 (24th September 2019) - Maleki, Mohammad Jafar; Ghasemi, Yaghoob; Pourhassan‐Moghaddam, Mohammad; Asadi, Nahideh; Dadashpour, Mehdi; Abolghasem Mohammadi, Seyed; Akbarzadeh, Abolfazl; Zarghami, Nosratollah
Abstract : Recently nanomaterials have attracted interest for increasing efficiency of polymerase chain reaction (PCR) systems. Here, the authors report on the usefulness of green graphene oxide/gold (GO/Au) nanocomposites for enhancement of PCR reactions. In this study, green GO/Au nanocomposite was prepared with Matricaria chamomilla extract as reducing/capping agent for site‐directed nucleation of Au o atoms on surface of GO sheets. The as‐prepared green GO/Au nanocomposites were then characterised with UV–VIS spectrophotometer and scanning electron microscopy. Later, the effect of these nanocomposites was studied on end‐point and real‐time PCR employed for amplification of human glyceraldehyde‐3‐phosphate dehydrogenase gene. The results indicated that GO/Au nanocomposite can improve both end‐point and real‐time PCR methods at the optimum concentrations, possibly through interaction between GO/Au nanocomposite and the materials in PCR reaction, and through providing increased thermal convection by the GO surface as well as the Au nanostructures. In conclusion, it can be suggested that green GO/Au nanocomposite is a biocompatible and eco‐friendly candidate as enhancer of in‐vitro molecular amplification strategies.